2022
DOI: 10.19160/e-ijer.1032214
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Research: Students’ Motivational Sources when Preparing for Centralized Exams in Turkey

Abstract: The aim of this research is to examine the positive and negative motivational sources of students with internal and external characteristics during the preparation process for national centralized exams in Turkey in the light of longitudinal data. The research is important in terms of revealing the sources of motivation for the national centralized exams, which have an important place regarding both the education system and shaping the future of the youth in Turkey. It is clear that an educational process with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 25 publications
0
1
0
1
Order By: Relevance
“…Vohns (2012) çalışmasında Rasch modeli ve bu modelin eğitimdeki kullanımı üzerine bir değerlendirme sunulmuştur. S. Ercan & Çakar (2021) ve Yakar (2022), öğrencilerin motivasyon ve başarılarını etkileyen faktörler üzerinde durmaktadır. Bu çalışmalarda elde edilen sonuçlar, bu araştırmanın sonuçlarını desteklememektedir.…”
Section: Discussionunclassified
“…Vohns (2012) çalışmasında Rasch modeli ve bu modelin eğitimdeki kullanımı üzerine bir değerlendirme sunulmuştur. S. Ercan & Çakar (2021) ve Yakar (2022), öğrencilerin motivasyon ve başarılarını etkileyen faktörler üzerinde durmaktadır. Bu çalışmalarda elde edilen sonuçlar, bu araştırmanın sonuçlarını desteklememektedir.…”
Section: Discussionunclassified
“…The results of a study by Williams & Dahan (2022) showed that students admitted through National Selection are more likely to have more widespread access to academic support resources. In addition, Yakar (2022) study revealed that students who choose the National Selection route often have higher motivation to achieve academic performance.…”
Section: Introductionmentioning
confidence: 99%